IMPLEMENTASI PESANTREN DALAM PENDIDIKAN KARAKTER SANTRI DI ERA DIGITALISASI: (Studi Kasus di Pondok Modern Al-Rifa'ie 2 Gondanglegi Kab. Malang) - Zulfan Syahansyah; Fatimatuzzahro (Pascasarjana Institut Agama Islam Al-Qolam, 2023)
Islamic boarding schools are educational institutions that play an important role in shaping the character of Islam that is friendly and tolerant. Maintaining the tradition that has been attached to a pesantren is now a challenge for pesantren in the current era of change. This paper is the result of research with a policy research flow that aims to describe and understand the Implementation of the Al-Rifa'ie Gondanglegi Malang Modern Islamic Boarding School in the Digital Age. By using qualitative research methods. The researcher examines the methods used by Pondok Modern Al-Rifa'ie in building moral character education for its students in the current Digital Age. The goal to be achieved from this research is to know and understand how Pondok Modern Al-Rifa'ie Gondanglegi Malang in fostering morals in the current digital era where technology is developing rapidly and has a very positive effect on Islamic boarding school students Al-Rifa'ie Gondanglegi Poor. The results of the author's research show that the implementation of Al-Rifa'ie Gondanglegi Malang Modern Islamic Boarding School is very active in embracing its students to be nurtured in morality by adjusting to the current era of digitalization which is developing rapidly so that it can very easily influence the morals of not only the students, but even all those who involved in Pondok Modern Al-Rifa'ie. Therefor Pondok Modern Al-Rifa'ie has prepared character building tips for students in the current digitalization era. Keywords: Islamic Boarding School, Santri Character Education, Digital Era